Child labor and the education of a society - Bell, Clive; Gersbach, Hans (Discussion paper series, 2001)
We examine economic growth, inequality and education when the wellspring of growth is the formation of human capital through a combination of the quality of child-rearing and formal schooling. The existence of multiple steady states is established, including a poverty trap, wherein children work full-time and no human capital accumulation takes place, with continuous growth at an asymptotically steady rate as an alternative. We show that a society can escape from the poverty trap into a condition of continuous growth through a program of taxes and transfers. Temporary inequality is a necessary condition to escape in finite time, but long-run inequalities are avoidable provided sufficiently heavy, but temporary taxes can be imposed on the better-off. Programs aiming simply at high attendance rates in the present can be strongly non-optimal.
Keywords: Arbeitspapier; Graue Literatur